Nomen est omen – Tourist image of the Balkans - Smith, Melanie; Sulyok, Judit; Jancsik, András; Puczkó, László; Kiss, Kornélia; Sziva, Ivett; Papp-VáryÁrpád Ferenc; Michalkó, Gábor (Hungarian Geographical Bulletin, 2018)
The regime change, the South Slavic civil war, global recession and their political, economic and social consequences had a significant impact on the tourism market of South-east Europe and the Balkan region. Many potential visitors to the region were affected by their negative associations with past events, even those that happened many years ago. The image of the Balkan region has become at times almost synonymous with conflict, turmoil and unrest. However, these perceptions may be changing and are therefore worthy of exploration. The article provides a tourism oriented analysis of the area’s image as a tourism destination. In accordance with the literature, the perceptions are measured by using a customer-based approach. Internet-based social media encourages the sharing of recent tourism experiences which can confirm or change associations with destinations. This study provides a content analysis of comments from one of the most popular travel portals (TripAdvisor) including key elements of the Balkan region’s image. The results of the research show theoretical implications like the importance of emotional image elements, the role of locals, or the complexity of tourism experience. From a practical point of view, the conclusions can induce long term thinking about the selected destination’s branding, and motivation for further research, as well.